Trajectories of Academic Performance Across Compulsory Schooling and Thriving in Young Adulthood. Issue 6 (22nd September 2018) - Tomasik, Martin J.; Napolitano, Christopher M.; Moser, Urs
Abstract : Thriving is a developmental process that is shaped by previous and current interactions within developmental contexts. We hypothesized that academic performance in the school context will positively predict thriving in young adulthood. Data of N = 2, 043 students from Zurich were assessed with standardized tests in Grades 1, 3, 6, and 9. Results showed that a stronger increase in academic performance significantly predicted thriving at age 20, even after statistically controlling for various covariates. Further analyses showed that school bonding might represent a mediating link between the academic performance and thriving. We argue that although schools can be considered the most widespread and intensive "youth development program" of sorts, their role for thriving has been largely neglected in developmental science.